MODELS AND METHODS OF STATISTICAL TREATMENT OF RESULTS OF THE CONTROLLED FROM DISTANCE DIAGNOSTICS OF LEVEL OF KNOWLEDGES - Безгачнюк, Юрій Володимирович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Models and methods of statistical treatment of results of the controlled from distance diagnostics of level of knowledges of students are considered in the article, and also realization of the proper vehicle in the system of d-tester, which is used on a department CT and SU IFNTOUNG during five years